The Influence of Science, Environment, Technology, Society (SETS) Learning Models on Learning Activities and Biology Learning Outcomes - Jumiah Az; Indayana Febriani Tanjung; Rohani Rohani (Magister Pendidikan Biologi, Universitas Negeri Medan, 2022)
This study aims to determine the effect of the Science, Environment, Technology, Society (SETS) learning model on learning activities and biology learning outcomes. The sample of this research was students of class VII totaling 30 students people. The research data collection method is using data collection instruments in the form of learning activity observation and a written test in the form of multiple choice. Methods of data analysis of learning activities using the formula Weight Means Score and data analysis of learning outcomes is done by using the